The impact of clergy sexual abuse on spirituality and health: A systematic scoping review of the literature - Joanne Durkin; Rachel Zordan; Matthew Bullen; Nadia Pavich; Patricia Therese Benedict Thomas; Carolyn Lethborg; Wendy Holder; Melinda Jolly; Darlene Dreise; Daniel Fleming (PLoS ONE, 2025)
Sexual abuse perpetrated by clergy or other Church leaders can cause harm to the spirituality of people who are subject to this abuse, which also has impacts on their overall health. We conducted a systematic scoping review to examine how Spiritual Harm in this context is operationalized in the literature with specific reference to the Catholic Church. Literature searches were conducted across Academic Search Complete, Informit Database, ProQuest, Web of Science and Google Scholar in 2022 and updated throughout 2023. Eligible studies were published between 2002–2022 and included peer reviewed empirical research, systematic reviews, discussion, or perspective papers that explored spiritual and/or religious harm and sexual abuse in a church context, and the psychological, emotional, and spiritual impact of the abuse. The review included 12 research articles. Data were analysed using qualitative approaches and presented as a narrative summary. Reporting follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for scoping reviews. Spiritual Harm in people who are subject to clerical sexual abuse is understood as a distinct condition or phenomena, comprising of complex spiritual, emotional and psychological components. However, it is not consistently defined. Understanding Spiritual Harm in a more comprehensive and consistent way is important in order to be able to adequately respond to the needs of victims, survivors, their families and wider communities.